FERREIRA, J. R. Eurípides: As suplicantes. 1. ed. Porto Alegre: Movimento, 2012. 78 p. ISBN 978-85-7195-150-1 - Salvador, Evandro Luis (Classica - Revista Brasileira de Estudos Clássicos, 2013)
Resenha de FERREIRA, J. R. Eurípides: As suplicantes. 1. ed. Porto Alegre: Movimento, 2012. 78 p. ISBN 978-85-7195-150-1